2005
DOI: 10.1002/app.22201
|View full text |Cite
|
Sign up to set email alerts
|

Photografting of N‐isopropylacrylamide and glycidyl methacrylate binary monomers on polyethylene film: Effect of mixed solvent consisting of water and organic solvent

Abstract: Photografting ( Ͼ 300 nm) of N-isopropylacrylamide (NIPAAm) and glycidyl methacrylate (GMA) binary monomers (NIPAAm/GMA) on low-density polyethylene film (thickness ϭ 30 m) was investigated at 60°C using mixed solvent consisting of water and an organic solvent such as acetone. Xanthone was used as a photoinitiator by coating it on the film surfaces. A maximum percentage of grafting was observed at a certain concentration of acetone in the mixed solvent, which was commonly observed for both ratios of NIPAAm/GMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 83 publications
0
9
0
1
Order By: Relevance
“…Therefore, photografting of GMA was carried out by varying the irradiation time with a GMA monomer solution prepared in an aqueous ethanol solution of 80 vol%. It has been reported by Irwan et al [44][45][46] and other researchers 47 that grafting behavior depends on the balance between the two effects of the mixed solvent consisting of water and an organic solvent. A positive effect of an increasing concentration of the organic solvent component in the mixed solvent is an increase in the solubility of the monomer used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, photografting of GMA was carried out by varying the irradiation time with a GMA monomer solution prepared in an aqueous ethanol solution of 80 vol%. It has been reported by Irwan et al [44][45][46] and other researchers 47 that grafting behavior depends on the balance between the two effects of the mixed solvent consisting of water and an organic solvent. A positive effect of an increasing concentration of the organic solvent component in the mixed solvent is an increase in the solubility of the monomer used.…”
Section: Resultsmentioning
confidence: 99%
“…To the contrary, the surface properties of the polyolefin materials modified by the grafting techniques should be preserved more durably than the surface modified by the techniques mentioned above. The grafting of various monomers on the polyolefin materials are initiated through plasma treatment 12 and irradiation with UV 13,[14][15][16][17][18] or Co 60 radiation [19][20][21][22] as an energy source.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of organic solvent, the affinity of the solvent with the polymeric substrates (Wang, Brown, & Li, 2007;Wang & Brown, 2004a;Yang & Ranby, 1999;Zhao et al, 2000) and the initiating ability of the solvents (Deng et al, 2000a) should be considered to raise the reactivity ratio. Additionally, by using the mixed solvent of water and an organic solvent, the affinity of the mixed solvent with the polymeric substrate could be precisely controlled, which may efficiently determine the location of the grafted chains (Deng et al, 2000a;Irwan et al, 2002Irwan et al, , 2003aIrwan et al, , 2003bIrwan et al, , 2004Irwan et al, , 2005Wang & Brown, 2004b, 2004c.…”
Section: Photo-grafting Polymerizations By Photo-initiatorsmentioning
confidence: 99%
“…As an alternative method, photoinitiator is precoated on the surface of a polymer substrate by immersing the polymer substrate in an organic solution containing the photoinitiator for a period of time and then drying it, then the photografting reaction can be carried out in mixed solvents containing water and organic solvents. Kubota and coworkers8–11 investigated the effect of mixed solvent of water and organic solvents, such as acetone, methanol, dioxane, and tetrahydrofuran (THF), on the photografting of hydrophilic monomers on polyethylene film precoated with Xanthone (XT). It was found that the component of the organic solvents in the mixed solvent remarkably influenced both the grafting behaviors and the location of the grafted chains in the PE film substrate.…”
Section: Introductionmentioning
confidence: 99%